Financial Integration in Asia : Recent Developments and Next Steps - Teo, Leslie (IMF Working Papers; Working Paper ;, 2006)
This Working Paper brings together three papers prepared as background for discussions at the Second High-Level Conference on Asian Integration cohosted by the Monetary Authority of Singapore and the IMF on May 25, 2006. The first documents recent trends in the intraregional flow of goods and capital and explores linkages between real and financial integration. The second focuses on the institutional and regulatory reforms needed to reap the benefits-and contain the risks-of financial integration in Asia. The third considers the implications of economic integration for the choice of the exchange rate regime and the conduct of macroeconomic policies.